Pemanfaatan Sampah Anorganik Rumah Tangga Menjadi Produk Kerajinan Berbasis Locality Development di RW 08 Kelurahan Sawangan Baru, Depok, Jawa Barat - Wibowo, Arif; Tsaqila, Hasna; Christiandi, Jeannette Anastasia; Afandi, Muhammad; Maulana, Ahmad (Jurnal Pengabdian Tri Bhakti, 2024)
The Community Empowerment Program with the theme of Utilization of Household Inorganic Waste into Craft Products Based on Locality Development carried out in RW 08, Sawangan Baru Village, Depok, West Java is a program initiated by the community and community assistance. This activity is an effort to overcome the waste problem in the RW 08 area, especially inorganic household waste. This activity is carried out by compiling several activities by implementing the stages in action research (look, think, and act). This activity resulted in several changes in knowledge and behavior, there was an increase in knowledge about processing inorganic waste into goods of economic value and there was a change in behavior in carrying out joint activities to achieve common goals where the values ​​of cooperation and working collaboratively began to grow among residents of RW 08. In addition, a social network was also built between the community and the local government which aims to obtain further guidance from the local government and access to funding and marketing of products produced by the community.